A christmas carol - Dickens, Charles; Lawrence, Micheal; Cottam, Martin (England Heinemann- Pearson eduacation limited, 1999)
"A Christmas Carol" by Charles Dickens tells the story of Ebenezer Scrooge, a miserly and greedy man, who is visited by the ghost of his deceased business partner, Jacob Marley, and the Ghosts of Christmas Past, Present, and Yet to Come.